Mapping the Organization of Atrial Fibrillation with Basket Catheters Part I: Validation of a Real-Time Algorithm - BARBARO, VINCENZO; BARTOLINI, PIETRO; CALCAGNINI, GIOVANNI; CENSI, FEDERICA; MORELLI, SANDRA; MICHELUCCI, ANTONIO (Pacing and clinical electrophysiology, 2001)
BARBARO, V., et al.: Mapping the Organization of Atrial Fibrillation with Basket Catheters Part I: Validation of a Real‐Time Algorithm. The authors proposed a real‐time algorithm to quantify AF organization from multielectrode basket catheter (MBC) recordings. The algorithm is based on a fast method to estimate the number of points along the baseline of a single bipolar electrogram (number of occurrences, NO). They have already proven this parameter to be effective at discriminating AF organization according to Wells' criteria. Special attention has been paid to ventricular far‐field artifacts, as they proved they can significantly bias the degree of organization. To fulfill the constraints of a real‐time application, a ventricular blanking procedure was implemented and validated. Bipolar electrograms were obtained from MBC in the right atrium in 17 informed patients with chronic AF. The results of NO computations were displayed as three‐dimensional color‐coded maps of organization by interpolating the measurements obtained at the locations of catheter bipoles. The proposed method allows real‐time estimation of the organization of the atrial electrograms according to Wells' criteria. The estimation has a temporal resolution of 2 seconds, is robust to far‐field ventricular artifacts, and interpolates the data available to furnish a single global map of the entire atrium. Further studies devoted to the analysis of individual and common patterns of the regional distribution of AF organization are needed to assess the usefulness of this approach for electrophysiological studies and therapeutic applications.